Human Perivascular Stem Cell‐Based Bone Graft Substitute Induces Rat Spinal Fusion. (25th August 2014) - Chung, Choon G.; James, Aaron W.; Asatrian, Greg; Chang, Le; Nguyen, Alan; Le, Khoi; Bayani, Georgina; Lee, Robert; Stoker, David; Pang, Shen; Zhang, Xinli; Ting, Kang; et al.
Abstract : Adipose tissue is an attractive source of mesenchymal stem cells (MSCs) because of its abundance and accessibility. We have previously defined a population of native MSCs termed perivascular stem cells (PSCs), purified from diverse human tissues, including adipose tissue. Human PSCs (hPSCs) are a bipartite cell population composed of pericytes (CD146+CD34−CD45−) and adventitial cells (CD146−CD34+CD45−), isolated by fluorescence‐activated cell sorting and with properties identical to those of culture identified MSCs. Our previous studies showed that hPSCs exhibit improved bone formation compared with a sample‐matched unpurified population (termed stromal vascular fraction); however, it is not known whether hPSCs would be efficacious in a spinal fusion model. To investigate, we evaluated the osteogenic potential of freshly sorted hPSCs without culture expansion and differentiation in a rat model of posterolateral lumbar spinal fusion. We compared increasing dosages of implanted hPSCs to assess for dose‐dependent efficacy. All hPSC treatment groups induced successful spinal fusion, assessed by manual palpation and microcomputed tomography. Computerized biomechanical simulation (finite element analysis) further demonstrated bone fusion with hPSC treatment. Histological analyses showed robust endochondral ossification in hPSC‐treated samples. Finally, we confirmed that implanted hPSCs indeed differentiated into osteoblasts and osteocytes; however, the majority of the new bone formation was of host origin. These results suggest that implanted hPSCs positively regulate bone formation via direct and paracrine mechanisms. In summary, hPSCs are a readily available MSC population that effectively forms bone without requirements for culture or predifferentiation. Thus, hPSC‐based products show promise for future efforts in clinical bone regeneration and repair. Abstract : This study evaluated the osteogenic potential of freshly sorted human perivascular stem cells (hPSCs) without culture expansion and differentiation in a rat model of posterolateral lumbar spinal fusion. All hPSC treatment groups induced successful spinal fusion, assessed by manual palpation and microcomputed tomography, suggesting that implanted hPSCs positively regulate bone formation via direct and paracrine mechanisms. Thus, hPSC‐based products show promise for future efforts in clinical bone regeneration and repair.